Dutch auction versus fixed-price self-tender offers for common stock - Kamma, Sreenivas; Kanatas, George; Raymar, Steven (Journal of Financial Intermediation, 1992)
This paper studies distinctions between fixed-price and Dutch auction self-tenders for common stock. We find that fixed-price tenders pay higher premiums to retire greater equity fractions than Dutch offers yet generate similar total returns to stockholders. Accordingly, total returns are significantly higher in Dutch auctions after controlling for tender and firm characteristics. In addition, wealth transfers to owners of repurchased shares are significantly higher in fixed-price offers. The Dutch mechanism thus appears to induce increases in firm value with smaller disbursals of cash. These cost savings to investors who maintain their ownership may explain the popularity of the new technique.